Composition of Royal Jelly (RJ) and Its Anti-Androgenic Effect on Reproductive Parameters in a Polycystic Ovarian Syndrome (PCOS) Animal Model - Norhamidar Ab Hamid; Ainul Bahiyah Abu Bakar; Anani Aila Mat Zain; Nik Hazlina Nik Hussain; Zaidatul Akmal Othman; Zaida Zakaria; Mahaneem Mohamed (MDPI AG, 2020)
Royal jelly (RJ) has been shown to contribute its positive effects upon imbalance in the reproductive system. However, it remains unknown as to whether RJ has an anti-androgenic effect on reproductive parameters in a polycystic ovarian syndrome (PCOS) animal model. Composition of RJ was assessed by phytochemical screening and the LC-MS method. Forty immature female rats (3 weeks, 40-50 g) were randomly divided into five groups (n = 8 per group), i.e., control, testosterone (T), T+100RJ (100 mg/kg/day), T+200RJ (200 mg/kg/day RJ), and T+400RJ (400 mg/kg/day RJ) groups. Hyperandrogenism was induced by daily subcutaneous injection of T propionate for 3 weeks, followed by oral RJ for 4 weeks. The T+200RJ group had a significantly higher follicle-stimulating hormone level, and significantly lower luteinizing hormone, testosterone, and estradiol levels in comparison to the T group. Malondialdehyde level and glutathione peroxidase activity were significantly lower, while total antioxidant capacity level was significantly higher in the T+200RJ group compared to the T group. Histologically, the T+200RJ group showed recovery of various stages of ovarian follicular development. RJ at 200 mg/kg/day for 4 weeks significantly improved reproductive parameters in PCOS rats partly due to its anti-androgenic effect through antioxidant action and probably due to modulation on estrogenic activity, which needs further study to evaluate its exact mechanism of action.